Scoping study for Chuine Wildlife Conservancy - Okoth, Owino J. (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This report documents a study undertaken to ascertain the opportunities and suitability of Chuine Wildlife Conservancy as a site for implementing participatory rangeland management (PRM).